The Role of Perception of Support in the Classroom on the Students’ Motivation and Emotions: The Impact on Metacognition Strategies and Academic Performance in Math and English Classes - Trigueros, Ruben; Aguilar-Parra, José M.; Lopez-Liria, Remedios; Cangas, Adolfo J.; González, Jerónimo J.; Álvarez, Joaquín F. (Frontiers in Psychology, 2020)
According to the latest PISA report and the Cambridge University Student Barometer, Spanish students have the worst academic results in mathematics and English among the European Union countries. The objective of this study has been to analyse the influence of the teacher on motivation, positive emotions, metacognition strategies and the academic performance of the students in those classes. We analysed responses from 604 students of English and 547 students of mathematics, aged between 13-19 years. The teacher plays a relevant role in the motivation and emotions generated in the students, issues that determine decision making in the students’ learning and academic performance.